Exact Solution of a Linear Difference Equation in a Finite Number of Steps - Skovpen, Sergey Mikhailovich; Iskhakov, Albert Saitovich (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
An exact solution of a linear difference equation in a finite number of steps has been obtained. This refutes the conventional wisdom that a simple iterative method for solving a system of linear algebraic equations is approximate. The nilpotency of the iteration matrix is the necessary and sufficient condition for getting an exact solution. The examples of iterative equations providing an exact solution to the simplest algebraic system are presented.